Expression of Cyclin D1 in normal and hyperplastic endometrium - Kundu, Parveen R.; Sindhu, Anjali; Kaur, Swaran; Kulhria, Amrita; Hooda, Ritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Endometrial hyperplasia is characterised by increased gland to stroma ratio with varying degree of atypia. Cyclin D1 is a protein playing important role during the G1→S phase transition in the cell cycle. The present study evaluated the expression of Cyclin D1 in normal and hyperplastic endometrium. Methods: A cross sectional study was conducted over a period of 1 year. We evaluated and compared the expression of Cyclin D1 in 56 endometrial samples including 24 cases of simple hyperplasia, 12 cases of complex hyperplasia and 10 cases each of secretory and proliferative endometrium. Results: A substantial increase in expression of Cyclin D1 was seen in hyperplastic endometrium compared to normal endometrium. Moreover, complex hyperplasia showed the maximum positivity for Cyclin D1. Conclusions: Cyclin D1 may play a stimulatory role in the proliferation of endometrial glands and hence may be involved in endometrial tumorigenesis.